PERILAKU TIDAK MEMILIH MASYARAKAT PADA PEMILIHAN KEPALA DESA SERENTAK TAHUN 2015 DI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Jhon Nefi Adrian; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study was backed by the village chief elections simultaneously by 2015 in accordance with the law number 6 Year 2014 Of the village. The election of village heads simultaneously also held in the village of Tarai Bangun subdistrict of Tambang Kampar districts. However, at the time of the election did not choose the behavior of the community is very high. Based on the background of the problem, then this research aims to find out the cause of the villagers did not choose the Tarai Bangun Subdistrict of Kampar Regency Tambang on the election of village heads simultaneously by 2015. Research methods used in the writing of this thesis is descriptive quantitative methods. The type of data in this study is the primary data and secondary data. Data collection techniques in the study is a questionnaire, interview and documentation. Data analysis technique used is descriptive quantitative.The results of this study indicate that the majority of the community does not choose behavior at the time of the election of village heads simultaneously in Tarai Bangun Village woke up feeling no fortunately and prefer the bustle of other or commonly called by a rational pragmatist. In addition most of the community does not choose is also caused by a lack of information or dissemination by Election Committee head of the village. Then other factors causing the high's behavior did not choose the public because most people do not know the candidates or candidate village head. It can be seen from the answers to the questionnaire the villagers Bangun Tarai. In this study the authors conclude that the rational factors of the community is the biggest factor that led to the community not to vote on the election of the village chief in the village of Tarai Bangun. In addition to this factor because the lack of socialization and psychological factors also became the cause of behavior did not choose people in the village of Tarai Bangun subdistrict of Tambang Kampar districts.Key Words: Behavior Not To Vote, The Election Of The Head Of The Village